A estética da cena na literatura de Sérgio Sant'Anna: considerações sobre A tragédia brasileira, Um crime delicado e O livro de Praga - Samira Pinto Almeida (2015)
This study aimed to contribute to the studies on the theatricality of Sergio Sant'Anna's literature from the reflection on the construction of the scene in the novels 'A tragédia brasileira!' (first edition in 1987), 'Um crime delicado' (published in 1997) and 'O livro de Praga' (2011). In the first phase of the research, we discussed the rise of the scene in art and contemporary reality. In this sense, the works in question were examined with subsides of valuable concepts to the field of performing arts and were also contemplated in the light of new forms of production and reception of the scene in our world - forms afforded mainly by technological development. In the second phase, we analyzed the introduction of the scene through the concept of simulacra, proposed by Baudrillard, term here understood as a phenomenon that undermines the alleged dichotomy between reality and fiction. In the third phase, we investigated the importance and the power of sight in the configuration of santanian spectacle. For this, we evaluated the effects of the scene on the characters and narrators through notions such as 'punctum', 'studium' and object a, as well as the link between the uniqueness of the look and the mask/persona adopted by fictional beings. Finally, in the fourth phase of the study, we considered the relationship between art and eroticism, body and thought in Sant'Anna's writing in order to highlight the different experiences gained both by distant and active spectators. In the novels analyzed, we found that the scene is established in the world of the characters through the interaction between aesthetic production and 'life' (the latter also understood, in the fictional reality, as art, spectacle), hence emerging the thought about artistic creation in its broader sense, about the pleasure obtained through contemplation of the created object; finally, about the experiences offered by the moment of creation and reception.